Building a DNA barcode reference library for the true butterflies (Lepidoptera) of Peninsula Malaysia: what about the subspecies? - Wilson, J.J.; Sing, K.W.; Sofian-Azirun, Mohd (Public Library of Science, 2013)
The objective of this study was to build a DNA barcode reference library for the true butterflies of Peninsula Malaysia and assess the value of attaching subspecies names to DNA barcode records. A new DNA barcode library was constructed with butterflies from the Museum of Zoology, University of Malaya collection. The library was analysed in conjunction with publicly available DNA barcodes from other Asia-Pacific localities to test the ability of the DNA barcodes to discriminate species and subspecies. Analyses confirmed the capacity of the new DNA barcode reference library to distinguish the vast majority of species (92) and revealed that most subspecies possessed unique DNA barcodes (84). In some cases conspecific subspecies exhibited genetic distances between their DNA barcodes that are typically seen between species, and these were often taxa that have previously been regarded as full species. Subspecies designations as shorthand for geographically and morphologically differentiated groups provide a useful heuristic for assessing how such groups correlate with clustering patterns of DNA barcodes, especially as the number of DNA barcodes per species in reference libraries increases. Our study demonstrates the value in attaching subspecies names to DNA barcode records as they can reveal a history of taxonomic concepts and expose important units of biodiversity.